How Indonesian Accounting Education Providers Meet The Demand of The Industry - Setyaningrum, Dyah; Muktiyanto, Ali; Hermawan, Ancella A. (Universitas Prasetiya Mulya, 2015)
The purpose of this study is to evaluate performance of accounting education providers in Indonesia in producing graduates required by the industry. This study compares different perception between the employers, lecturers, junior auditors and students regarding: (1) auditors’ early employment problem; (2) university performance; and (3) university improvement. We employ quantitative methods to present descriptive analysis of different perceptions of stakeholders regarding university performance. The top early employment problem of the newly hires auditor is problems with orientation and adaptation with new working environment; technical competence and soft-skill problem. Although all respondent agree that university performed well in preparing graduates for the job market, but graduates still lacking in several factors (technical skills and soft-skills) that university need to overcome. Suggestions for university improvement in order to producing graduates required by the industry are: (1) incorporate internship as compulsory subjects; (2) partnership with public accounting firm in recruitment process; (3) practical training with real audit cases via seminar/workshop; (4) student-centered learning approach; and (5) regular updates of current audit practice to lecturer.